Star Forming Rates and HI Gas Content in Galaxy Groups - Martens, Sarah Katherine (Proceedings of the Wisconsin Space Conference, 2016)
We compare the star formation rates with the respective HI properties of 4854 galaxies in 743 different groups. Using data from the SDSS and the GALEX all sky survey (AIS) we measure the star formation rates and NUV-r colors as a function of the total group mass, position within the group, and HI content as derived from the Arecibo Legacy Fast ALFA (ALFALFA) survey. The NUV-r colors are consistent with star forming field galaxies. We show how the quenching of the star formation is correlated with galaxy HI content and how both are affected by a group environment.Â  Â 